802. Use of N-Acetylcysteine for Prevention and Treatment of Isoniazid Induced Liver Injury During Treatment of Mycobacterial Infections. (26th November 2018) - Diaz, Heidi Torres; Serrano, Ruth; Bowling, Jason E; Anstead, Gregory; Javeri, Heta
Abstract: Background: Hepatotoxicity secondary to therapy for Mycobacterium tuberculosis (MTB) is a common complication that may lead to treatment interruption. N -Acetylcysteine (NAC) exerts a hepatoprotective effect by repleting glutathione stores and enhancing the cellular antioxidant defense mechanism. NAC has been found to be protective against liver toxicity in animals treated for MTB infection. Randomized controlled trials have shown that its use in humans also decreases the risk of hepatotoxicity associated with anti-MTB treatment but there is minimal data regarding its utility for treatment of liver toxicity. Methods: Patients who received NAC from January 2012 to March 2018 for prophylaxis and treatment of increasing liver function tests (LFTs) while on isoniazid (INH) were included. A retrospective review of the medical record system was performed. Results: Nineteen patients were included. Eight received NAC for treatment. The average age was 49 years. Seventy percent of patients were male. The mean BMI was 25. Five patients had underlying liver cirrhosis and two had hepatic steatosis. Eleven patients had Hepatitis C (HCV) and one had active Hepatitis B infection. Ten patients had MTB pulmonary infection, thee had latent TB infection, two meningitis, and three had disseminated disease. One patient was treated for atypical mycobacterial infection. The dose of NAC used was 600 mg oral twice daily and the duration was variable. The prophylaxis group had stable LFTs during treatment, except for two patients whose enzymes increased more than three times the upper limit of normal. These two patients had underlying HCV and liver cirrhosis. Only one required discontinuation of INH. This group received NAC for an average of 47 days. The treatment group had a favorable trend of liver enzymes after NAC initiation, with levels significantly improving by day 14 (Figures 1 and 2). Three patients did not require discontinuation of antibiotics. INH was stopped prior to NAC initiation in four patients. No side effects of NAC were documented in any patient. Conclusion: NAC is a safe and effective measure to prevent and treat hepatotoxicity secondary to INH therapy. More studies are needed to determine its optimal dose and duration for this indication. Disclosures: All authors: No reported disclosures.